2019
DOI: 10.2174/1745017901915010075
|View full text |Cite
|
Sign up to set email alerts
|

The Perception of Physical Health Status in Obsessive-Compulsive Disorder: A Systematic Review and Meta-Analysis

Abstract: Background:Physical Health Status is a neglected outcome in clinical practice with Obsessive-Compulsive Disorder (OCD) and a systematic review is lacking.Objective:The current study presents the first systematic review and meta-analysis summarizing the evidence on (a) perceived Physical Health Status, Bodily Pain and Role Limitations due to Physical Problems in patients with OCD compared with controls, (b) age, gender, severity of OCD symptoms, study publication date, study methodological quality as moderators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…First, healthcare costs in the OCD group were more than twice higher on average and was the largest total cost difference between the groups. In addition to a higher need for psychiatric services, previous research has indicated that individuals with OCD perceive their somatic health status as being worse, and experience more physical problems and pain than controls [ 22 ]. There is also evidence that individuals with OCD have a higher risk for obesity, type-2 diabetes and cardiovascular disorders, compared with the general population, which are already apparent in childhood and adolescence [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, healthcare costs in the OCD group were more than twice higher on average and was the largest total cost difference between the groups. In addition to a higher need for psychiatric services, previous research has indicated that individuals with OCD perceive their somatic health status as being worse, and experience more physical problems and pain than controls [ 22 ]. There is also evidence that individuals with OCD have a higher risk for obesity, type-2 diabetes and cardiovascular disorders, compared with the general population, which are already apparent in childhood and adolescence [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%